The Impact of Frontier Technology Adoption on Gender Inequality: Evidence from Africa - Pamela E. Ofori; Isaac K. Ofori (ZBW - Leibniz Information Centre for Economics, 2024)
The surge in frontier technology adoption (FTR) in education, health, and labour markets cannot be overemphasised. Notwithstanding, rigorous empirical findings concerning their socioeconomic impacts in the Global South are hard to find. Accordingly, this study explores the impact of FTR on gender inequality in low-income, and middle- and high-income African countries. Second, this study investigates the moderating role of electricity access in the FTR-gender inequality nexus. Third, the study examines the threshold effect of electricity access in the FTR-gender inequality relationship. Compelling evidence, based on country-level data for 29 African countries from 2010-2020, reveals that FTR promotes gender equality in both low-income, and middle- and high-income African countries. However, this impact is striking in the middle- and high-income African countries. Further, the contingency analysis establishes that electricity access amplifies the effect of FTR on gender equality but only in middle- and high-income African countries. Additionally, the threshold analysis demonstrates that broadening electricity access coverage conditions FTR to further enhance gender equality. However, this positive impact eludes low-income African countries. We conclude that investments in broadening electricity access and the capacity of African countries in adopting, mastering, and adapting frontier technologies are critical for inclusive human development.
Keywords: J16; O3; O55; Q01; Q43; 330; Africa; Agenda 2063; Frontier technology adoption; Gender Inequality; Inclusive human development